Communication Management of the General Election Commission (KPU) of Tanah Bumbu in the Candidate Selection Stage for the 2024 Regional Head Selection - Bustanul Mubarok; Aminah Swarnawati; Harmonis Harmonis (Riviera Publishing, 2025)
The regional head election (Pilkada) is a competitive electoral contest that requires proper management. One of the most crucial aspects is the communication management of the General Election Commission (KPU), which is the organizing body of the election. The KPU Tanah Bumbu, responsible for conducting the Pilkada in Tanah Bumbu Regency, South Kalimantan, has implemented communication management strategies tailored to various challenges and the local political dynamics. This study aims to assess the strategy, effectiveness, and challenges of the communication management of the General Election Commission (KPU) of Tanah Bumbu Regency during the candidate nomination stage of the 2024 Pilkada. This research was conducted in Tanah Bumbu Regency during the nomination phase of the 2024 Pilkada candidates. The study employs a qualitative descriptive method with a case study approach. Data collection techniques include in-depth interviews, observations, and documentation analysis. The theoretical framework applied in this study is George J. Terry's (2019) communication management theory, which includes four key components: planning, organizing, actuating, and controlling. The findings reveal that the communication management strategy of KPU Tanah Bumbu relies on highly competent communicators, adequate technological support, strong collaboration with relevant stakeholders, and sufficient funding. Additionally, the study found that KPU Tanah Bumbu has implemented effective communication management during the nomination stage of the 2024 Pilkada, covering all phases—planning, organizing, execution, mobilization, and evaluation. Furthermore, the research identified the main challenges in KPU Tanah Bumbu’s communication management, including low public literacy levels, infrastructure barriers, and unpredictable socio-political dynamics.